2008
DOI: 10.1177/104063870802000124
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiosarcoma in the Nictitating Membrane of a Horse

Abstract: Abstract. A 15-year-old Haflinger gelding presented with a mass in the left nictitating membrane. Two biopsies and the excised nictitating membrane were taken at different time points as a result of reoccurrence of the mass and submitted for histopathologic evaluation. The horse was euthanized as a result of poor prognosis following the reoccurrence of the mass after surgical removal. Histologically, the mass consisted of dilated, thin-walled vascular clefts and channels, lined by flattened to cuboidal endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A single case of lymphangiosarcoma affecting the ocular tissues has been reported in a cow . Lymphangiosarcoma is uncommonly reported in horses, and to the authors’ knowledge, only one case has been reported involving ocular tissues with no evidence of involvement of other tissues in that case . In nonocular equine cases, extensive visceral involvement has been reported .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A single case of lymphangiosarcoma affecting the ocular tissues has been reported in a cow . Lymphangiosarcoma is uncommonly reported in horses, and to the authors’ knowledge, only one case has been reported involving ocular tissues with no evidence of involvement of other tissues in that case . In nonocular equine cases, extensive visceral involvement has been reported .…”
Section: Introductionmentioning
confidence: 81%
“…In general, tumors of lymphatic origin are extremely uncommon in horses, with only four cases of lymphangiomas and three cases of lymphangiosarcomas reported . In the reported cases of lymphangioma, distant metastases were not documented and surgical excision was the recommended treatment; however, surgical removal was limited by size and location of the growths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equine ocular HSA is a rare malignant tumor of vascular endothelial origin 1 . LSA is another type of malignant ocular neoplasm identified in the horse, 4,6 which originates from the lymphatic system and may appear grossly and microscopically similar to HSA 5 . Histopathologic evaluation and IHC are often required to differentiate between equine ocular HSA and LSA.…”
Section: Discussionmentioning
confidence: 99%
“…Other tumours affecting the nictitans include lymphangiosarcoma (Puff et al . ), lymphangioma (Gehlen and Wohlsein ), papilloma (Lavach and Severin ; Junge et al . ), haemangiosarcoma (Sansom et al .…”
Section: Introductionmentioning
confidence: 99%